Terrorism, Guerrilla, and the Labeling of Militant Groups - Berger Hobson, Ronit (Terrorism and political violence, 2024)
Terrorist organizations are presumed to specialize in the planning and execution of acts of terrorism, but to what extent do these groups actually employ terrorism? The answer can help inform the debate over whether such groups should be labeled terrorist organizations at all. We explore these questions by examining the relative use of terrorism vis-à-vis guerrilla tactics among 1,013 groups listed in the Global Terrorism Database from 1970 to 2019. We find, first, that “terrorist groups” have historically relied on a combination of terrorist and guerrilla tactics. Second, while terrorism has been the preferred mode of warfare in the first four decades examined, guerrilla tactics have predominated in the 2010s. Our findings imply that the use of the “terrorist group” label had empirical justifications in the first four, although not the most recent decade under review. The data support calls for the adoption of value-neutral labels for contemporary militant groups.